Sperm cryopreservation in three species of endangered gazelles (Gazella cuvieri, G. dama mhorr, and G. dorcas neglecta). - Garde, J; Soler, A; Cassinello, J; Crespo, C; Malo, A; Espeso, G; Gomendio, M; Roldan, E (2003)
Long-term storage of semen by cryopreservation, with high recovery rates on thawing, is essential for the establishment of genetic resource banks of endangered species. The purpose of the present study was to evaluate various diluents for the cryopreservation of spermatozoa from three species of gazelles (genus Gazella) in a captive breeding program. The diluents compared were Tes (N-tris(hydroxymethyl)methyl-2 aminoethane sulfonic acid)-Tris with 5% egg yolk and 6% glycerol (TEST) and Triladyl, yolk-citrate, Tris-trehalose, and Tris-lactose-all of them with 20% egg yolk and 6% (Triladyl) or 8% glycerol. Semen was obtained by electroejaculation from 12 G. cuvieri, 12 G. dama, and 13 G. dorcas males. Samples with less than 50% motile sperm, positive endosmosis, or acrosome integrity were not used. Diluted samples were loaded into 0.25-ml straws, cooled slowly to 5 degrees C over 1.5 h (-0.16 degrees C/min), equilibrated at that temperature for 2 h, frozen in nitrogen vapors for 10 min, and plunged into liquid nitrogen. Subsamples were assessed fresh, after refrigeration-equilibration, after freezing and thawing, and 2 h after thawing. Differences were seen between diluents, with best overall recovery rates after freezing and thawing found with Triladyl, TEST, and Tris-trehalose in G. cuvieri, TEST in G. dama, and Triladyl and TEST in G. dorcas. Differences were observed between species in the ability to withstand freezing and thawing, with best results seen in G. dorcas, intermediate results in G. dama, and worst results in G. cuvieri. These differences were inversely related to the average values of inbreeding of these populations. The underlying mechanism responsible for these differences may be a differential resistance to osmotic shock.